Analisis Kinerja Keuangan Berdasarkan Rasio Keuangan pada PT Kimia Farma Tbk tahun 2016-2020 - Bilqist Luthfia Rachmi; Ade Ali Nurdin; Banter Laksana (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research aims to determine financial performance in PT Kimia Farma Tbk Ltd years 2016-2020 which is reviewed through financial ratios, that is: (1) Liquidity Ratio accounted for by Current Ratio and Cash Ratio, (2) Solvency Ratio accounted for by Total Equity to Assets Ratio and Debt to Assets Ratio, (3) Activity Ratio accounted for by Assets Turnover Ratio, Receivable Turnover Ratio and Inventory Turnover Ratio, (4) Profitability Ratio accounted for by Net Profit Margin, Return On Investment and Return on Equity, (5) Market Value Ratio accounted for by Earning Per Share, Price Earning Ratio and Price Book Value. The method used is descriptive quantitative with the object in the form of the financial statements of PT Kimia Farma Tbk 2016-2020. The technique used is documentation and literature study. The data analysis method used is quantitative descriptive analysis technique. The condition of the company's financial performance based on the ratio calculation can be concluded in the poor category, because in the last 5 years the average has decreased in terms of Liquidity Ratio 10.98%, Solvency 4.25%, Activity 7.30%, Profitability is 14.42 % and overall Market Value Ratio decreased.